Targeted therapy in advanced melanoma with rare BRAF mutations - Menzer, Christian; Menzies, Alexander M.; Carlino, Matteo S.; Reijers, Irene; Groen, Emma J.; Eigentler, Thomas; de Groot, Jan Willem B.; van der Veldt, Astrid A.M.; Johnson, Douglas B.; Meiss, Frank; Schlaak, Max; Schilling, Bastian; et al. (Journal of clinical oncology. [Englische Ausgabe], 2019)
PURPOSE: BRAF/MEK inhibition is a standard of care for patients with BRAF V600E/K-mutated metastatic melanoma. For patients with less frequent BRAF mutations, however, efficacy data are limited.METHODSIn the current study, 103 patients with metastatic melanoma with rare, activating non-V600E/K BRAF mutations that were treated with either a BRAF inhibitor (BRAFi), MEK inhibitor (MEKi), or the combination were included. BRAF mutation, patient and disease characteristics, response, and survival data were analyzed.RESULTSFifty-eight patient tumors (56%) harbored a non-E/K V600 mutation, 38 (37%) a non-V600 mutation, and seven had both V600E and a rare BRAF mutation (7%). The most frequent mutations were V600R (43%; 44 of 103), L597P/Q/R/S (15%; 15 of 103), and K601E (11%; 11 of 103). Most patients had stage IV disease and 42% had elevated lactate dehydrogenase at BRAFi/MEKi initiation. Most patients received combined BRAFi/MEKi (58%) or BRAFi monotherapy (37%). Of the 58 patients with V600 mutations, overall response rate to BRAFi monotherapy and combination BRAFi/MEKi was 27% (six of 22) and 56% (20 of 36), respectively, whereas median progression-free survival (PFS) was 3.7 months and 8.0 months, respectively (P = .002). Of the 38 patients with non-V600 mutations, overall response rate was 0% (zero of 15) to BRAFi, 40% (two of five) to MEKi, and 28% (five of 18) to combination treatment, with a median PFS of 1.8 months versus 3.7 months versus 3.3 months, respectively. Multivariable analyses revealed superior survival (PFS and overall survival) with combination over monotherapy in rare V600 and non-V600 mutated melanoma.CONCLUSIONPatients with rare BRAF mutations can respond to targeted therapy, however, efficacy seems to be lower compared with V600E mutated melanoma. Combination BRAFi/MEKi seems to be the best regimen for both V600 and non-V600 mutations. Yet interpretation should be done with care because of the heterogeneity of patients with small sample sizes for some of the reported mutations.
Gesehen am 18.03.2020